The Impact of Economic Incentives on Small and Medium Enterprises in Oman During COVID-19: Applied Study, Case of Dhofar Governorate in Oman (American Journal of Economics and Business Innovation, 2024)
The study examined the impact of economic inducement on small and medium enterprises (SMEs) in Dhofar Governorate, Oman, during the COVID-19 pandemic. Two variables were adopted: economic incentives as the independent variable and the recovery of SMEs as the dependent variable. Three dimensions were adopted to evaluate the economic incentives experienced by small and medium enterprises, which are “facilitation of granting loans,” “reducing taxes and fees,” and “technical assistance.” The study population consisted of the employees of 8 SME companies. Primary data was collected from a convenient sample of 104 via electronic questionnaire (due to the directives related to social distancing in light of the global health crisis (Covid 19). Data were evaluated through Statistical Packages for Social Sciences SPSS. The study found a strong correlation (90.9%) between economic incentives and the recovery of minor and medium enterprises. Key factors such as facilitating loans, reducing taxes and fees, and providing technical assistance had a strong impact (82.1%) on their recovery. The Omani government should prioritize projects based on local labor and supply chains to reduce leakages and create short-term jobs, enhancing household income during the pandemic. The study facilitates data analysis and obtaining clear results of the impact of economic incentives by using a descriptive-analytical method.Governments must execute fiscal and procedural stimulus to regain lost yield potential from COVID-19, considering the macroeconomic context, monetary policy, debt, trade globalization, and SDGs.